2021
DOI: 10.1177/0044118x211058225
|View full text |Cite
|
Sign up to set email alerts
|

A Service Model for Self-Directed Learning of NEET Youth at the Local Government Level

Abstract: Given the increasing value of lifelong learning, self-directed learning (SDL) has become increasingly relevant over time. In rural areas with limited service resources, the main approach to NEET-youth depicts them more as young people in need, and less as people with the potential for self-development and participation in lifelong learning. The growing importance of people’s return to education, flexible learning paths, and the need for quick adaptation and re-training in a rapidly changing society emphasizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To ensure the return of young people who fall within the NEET category back into society, there is an obvious need for service innovation (Kõiv et al, 2022). A recent review of Nordic research literature (Frøyland et al, 2022, p. 120) indicated that while the inclusion issue is extensive, problematic and resource-demanding, it is nonetheless possible to solve via a number of constructive measures and efforts.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the return of young people who fall within the NEET category back into society, there is an obvious need for service innovation (Kõiv et al, 2022). A recent review of Nordic research literature (Frøyland et al, 2022, p. 120) indicated that while the inclusion issue is extensive, problematic and resource-demanding, it is nonetheless possible to solve via a number of constructive measures and efforts.…”
Section: Introductionmentioning
confidence: 99%